دراسة تاثير المتضمنات اللامعدنية على مطروقات الفولاذ واطئ التسبيك - حسين عتيوي, علي; عبود عباس, ستار; عجيب كاصد, صباح (Journal of Engineering and Sustainable Development, 2022)
The non-metallic inclusions can be found in steel as a result of existence of oxygen and sulpher in form of oxides and sulphides which they have relative low solubility. The shape, number, size and distribution of these inclusions have a significant influence on the type and comportment of steel in various engineering applications.The object of this study is to examine the shape and type of the non-metallic inclusions by using chemical reagents and to determine the indices k0 and k1 which give the percentage amount of these inclusions in the structure of wrought low alloy steel(32Ni Cr MoV12.3), then to investigate the relation between these indices and mechanical properties.